Hubungan Empati dan Perilaku Perundungan pada Remaja - Siti Nurjannah; Kus Hendar; Ika Ariyati (Journal of Society Counseling, 2026)
This study examines the correlation between empathy and bullying behavior among students at SMP Ma’arif 1 Metro. Bullying in school environments has become an increasing concern due to its negative impact on students’ psychological well-being. Previous studies suggest that empathy plays a crucial role in shaping social behavior; however, empirical findings regarding its relationship with bullying remain inconsistent. Employing a quantitative approach, this study involved a population of 321 students, with a sample of 178 students selected for analysis. Data were collected using validated instruments, including a 10-item empathy scale and a 15-item bullying behavior scale. Due to non-normal data distribution (p = 0.019), the analysis was conducted using Spearman's rank correlation. The findings reveal that both empathy and bullying behavior are at a moderate level, and there is a significant but weak positive correlation between the two variables (rₛ = 0.268, p < 0.05). This result indicates a complex relationship between empathy and bullying behavior, suggesting that other psychological or social factors may influence this association. These findings highlight the importance of considering multiple factors in developing interventions to reduce bullying, rather than focusing solely on enhancing empathy